The Influence of Human Resources Quality On Performance By Mediation of Productivity In The New Normal Era at Bank Pembangunan Daerah Jawa Timur Tbk Malang Branch - Eko Putri, Ratih Puspitasari; Sawitri, Dyah (Green Publisher Indonesia, 2022)
This study aims to analyze the effect of quality of human resource on productivity, quality of human resource on performance, productivity on performance, and quality of human resource on performance with the mediation of productivity in the new normal era at PT Bank Pembangunan Daerah Jawa Timur Tbk Malang Branch. The research method used is path analysis on 64 respondents with purposive sampling method. The results showed that the quality of human resources has an effect on productivity, the quality of human resources has an effect on performance, productivity has an effect on performance, and the quality of human resources has an effect on performance with the mediation of productivity in the new normal era at PT Bank Pembangunan Daerah Jawa Timur Tbk Malang Branch